Horizontal advection of temperature and salinity by Rossby waves in the North Pacific. Issue 8 (18th April 2018) - Belonenko, Tatyana V.; Bashmachnikov, Igor L.; Kubryakov, Arseny A.
ABSTRACT: The Aquarius satellite has been used for the first time to characterize Rossby waves in sea surface salinity (SSS) measurements for the North Pacific Ocean. Westward propagating wave signals are delineated by the SSS zonal salinity gradients. The phase velocities and spectral properties obtained from zonal salinity gradients are closely correlated with corresponding values obtained from the sea surface temperature (SST) zonal gradient and the altimetry-derived meridional velocity. The westward propagating SSS signals are consistent with Rossby wave advection across the strong meridional gradients of water characteristics. Following Killworth, we attempted to provide satellite-based estimates of the contribution of horizontal Rossby wave advection to the surface transfer of temperature and salinity in the North Pacific Ocean. Westward propagating signals in the SST and SSS zonal gradient fields show that the observed intensity of meridional advection by the ambient gradients of SST and SSS is less than the intensity predicted by an analytical solution of the transfer equation for Rossby waves. Our results extend the previous studies of physical mechanisms of Rossby wave manifestation at the sea surface and we demonstrate that Rossby waves are responsible for low-frequency oscillations in SST and SSS concentration in the North Pacific.